Probiotic Property of Lactobacillus spp Isolated from Different Food Samples - Adhikari, Swesha; Adhikari, Sushma; Bohara, Chandra; Adhikari, Sushan; Neupane, Surendra; Pant, Om Prakash; Manandhar, Sarita (Journal of Institute of Science and Technology, 2025)
Lactic acid bacteria (LAB) are Gram-positive, non-sporing cocci or rod-shaped bacteria that produce lactic acid as a primary metabolic product and are recognized for their probiotic potential. This study aimed to isolate, screen, and identify LAB from 20 indigenous fermented food samples, including fermented leafy vegetable (Gundruk), yogurt (Dahi), bamboo shoot (Tama), pickle (Achar), and fresh cabbage. A total of 15 LAB isolates were identified based on Gram staining and biochemical tests. Their probiotic properties were evaluated through resistance to gastric pH 3.5 (9 isolates survived for 90 min), bile salt tolerance at 0.3% concentration (4 isolates exhibited strong growth), and NaCl tolerance at 2% and 4% concentrations (all isolates survived, but none at 6.5%). Antibiotic susceptibility testing revealed that all isolates were sensitive to ampicillin, gentamicin, erythromycin, ciprofloxacin, and oxacillin. Antibacterial activity assays demonstrated that LAB strains inhibited pathogenic bacteria, with inhibition zones ranging from 10 to 20 mm. Notably, two LAB isolates exhibited the strongest probiotic properties based on acid, bile, and NaCl tolerance, as well as antibacterial activity. These findings highlight the potential of indigenous fermented foods as a natural source of probiotic LAB strains.